Legal Gap In The Determination of Moderate Wound By Forensic Doctors On Visum Et Repertum In Criminal Case - Wahyu Putra Pratama, S.Kep (Faculty of Law, Merdeka University Surabaya, 2021)
The present research is about “Legal Gap in Determination of Moderate Wounds by forensic pathologists on Visum Et Repertum in Criminal Court”. There is a problem that legal concept of moderate wound on visum et repertum and legal gap for determining the state of moderate wounds by forensic pathologists at Visum et Repertum. This is a normative research with conceptual approach, statute approach, and case approach. Legal experts acknowledge moderate wound, which is a kind of wound or injury in between a minor and severe conditions. A legal gap created by the absence of moderate wound in law which is a familiar term criminal court. Regarding forensic pathologists competensies, they determine moderate injuries victims whose have economic impaired without physical disturbance.